2010
DOI: 10.1016/j.ijrobp.2009.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasonic Evaluation of Radiation-Induced Late Tissue Toxicity: Pilot Study of Breast Cancer Radiotherapy

Abstract: Purpose-To investigate the use of advanced ultrasonic imaging to quantitatively evaluate normaltissue toxicity in breast-cancer radiation treatment.Methods and Materials-Eighteen breast cancer patients who received radiation treatment were enrolled in an IRB-approved clinical study. Radiotherapy involved a radiation dose of 50.0-50.4 Gy delivered to the entire breast, followed by an electron boost of 10.0-16.0 Gy delivered to the tumor bed. Patients were scanned with ultrasound during follow-up that ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
1
36
0
2
Order By: Relevance
“…12,13 Ultrasound parameters were computed from RF data using in-house MATLAB software. Skin thickness was determined from the product of the ultrasound wave propagation speed in breast tissue, and the time interval between RF signal interaction between the epidermis and hypodermis.…”
Section: Quantitative Toxicity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Ultrasound parameters were computed from RF data using in-house MATLAB software. Skin thickness was determined from the product of the ultrasound wave propagation speed in breast tissue, and the time interval between RF signal interaction between the epidermis and hypodermis.…”
Section: Quantitative Toxicity Assessmentmentioning
confidence: 99%
“…[11][12][13][14] Skin thickening is a well-known response to radiation that may be measured by the distance between the radio-frequency (RF) echo from the skin's surface and from that of the hypodermis. Radiation-induced damage to the basal layer of dermal cells results in a blurred and irregular dermal-hypodermal interface on B-mode ultrasound images.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, the STRA has correlated with RTOG grading criteria of radiotherapy-induced skin toxicity in breast cancer patients. (18,21) Therefore, STRA served as an objective measure of XRT-induced skin toxicity in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Although recognized for decades, the assessment of skin toxicity is carried out subjectively by physicians through visual evaluation and palpation. We, along with other researchers (Huang et al 2007; Liu et al 2010; Warszawski et al 1998; Zhou et al 2009), have recently reported that ultrasound can be used to quantitatively assess skin toxicity after radiotherapy for breast cancer. In particular, skin thickening was observed in almost all post-radiotherapy patients (Huang et al 2007; Liu et al 2010), making it an important parameter in ultrasonic evaluation of skin toxicity.…”
Section: Introductionmentioning
confidence: 92%